Vertebrobasilar Dolichoectasia, An Unusual Cause of Trigeminal Neuralgia: A Case Report - Pradana, Wisniardhy Suarnata; Yueniwati, Yuyun (Department of Radiology, Medical Faculty, University of Brawijaya, 2022)
Background: Trigeminal neuralgia is a facial pain syndrome that generally occur unilateral following the sensory distribution of the trigeminal nerve. It is classified into trigeminal neuralgia with no apparent cause, classic trigeminal neuralgia, which is caused by vascular compression of the trigeminal nerve root, and secondary trigeminal neuralgia caused by major neurological diseases such as cerebellopontine angle tumour or multiple sclerosis.Case: A 60 years old male, complained of pain in the right face since >4 years ago, intermittent, radiating from around the upper right molars to the right face, like an electric shock, and appeared mainly when chewing. MRI and MRA examination of the patient revealed vertebrobasilar dolichoectasia causing displacement of the pons and right trigeminal nerve.Discussion: Vascular compression of the trigeminal nerve root is the most common cause of trigeminal neuralgia, which is commonly caused by small arteries such as the superior cerebellar artery. Vascular compression due to large arteries such as the basilar and vertebral arteries may occur in a minority of cases. MRI is an examination that plays an important role in cases of trigeminal neuralgia, because it can assess the pathology of cerebellopontine angle area, as well as assess the presence of neurovascular compression and morphological changes of the trigeminal nerve roots.